2017
DOI: 10.1111/1747-0080.12369
|View full text |Cite
|
Sign up to set email alerts
|

Delayed postoperative diet is associated with a greater incidence of prolonged postoperative ileus and longer stay in hospital for patients undergoing gastrointestinal surgery

Abstract: This retrospective study of current practice in a secondary-care general hospital highlights the gap between traditional care and the improved outcomes reported in the literature when early feeding practices are adopted after GI surgery. Further investigation of barriers and enablers is necessary to provide insight into developing the most appropriate strategy to achieve this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(134 reference statements)
0
6
0
1
Order By: Relevance
“…Of all POI cases, 28.2% (77/273) met the definition of SPOI: 18.2% (14) were hip procedures, 20.8% (16) were knee procedures, 54.5% (42) were spine procedures, and 6.5% (5) were other orthopedic procedures (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all POI cases, 28.2% (77/273) met the definition of SPOI: 18.2% (14) were hip procedures, 20.8% (16) were knee procedures, 54.5% (42) were spine procedures, and 6.5% (5) were other orthopedic procedures (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…This study was retrospective, and delayed feeding was one of our criteria for SPOI, and so whether there is a causal link cannot be established. However, early post-operative feeding has been found to decrease the rates of ileus, and studies evaluating more aggressive refeeding in elective orthopedic patients should be undertaken [3, 6, 16]. Regardless, slow refeeding is an easy-to-identify red flag for SPOI.…”
Section: Discussionmentioning
confidence: 99%
“…The dietary principles were stated in each diet category. A survey [ 10 ] revealed that many patients knew what they could not eat during their hospital stay, but what puzzled them was the food suitable for eating. Therefore, in each food category, we not only listed foods that were restricted but also foods that were suitable for eating ( Figure 1 ).…”
Section: Design Of Perioperative Health Education On a Mobile Platformmentioning
confidence: 99%
“…A wide variety of cutoff times and criteria have been used by studies to determine PPOI; however, 8-32% of patients suffer from PPOI following surgery. [4][5][6][7][8][9][10][11][12][13] PPOI is known to burden both patients and the health care system. Numerous studies have reported that patients with PPOI are prone to develop postoperative complications 4,9,13 that can lead to negative outcomes such as a prolonged length of stay [9][10][11] , increased reoperation rate and readmission rate 6,9,11,14 , and increased mortality rate.…”
Section: Introductionmentioning
confidence: 99%